KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA KELAS XI PMIA MAN TANJUNG MORAWA PADA PEMBELAJARAN SEL DENGAN MODEL PBL BERBANTUAN LKS - Windi Novia Sari; Melva Silitonga (Universitas Negeri Medan, 2017)
This study aims to describe high order thinking skills students of class XI PMIA MAN Tanjung Morawa on cell learning with LKS assisted model PBL. This study included pre-experiment type with one group pretest posttest design and was conducted in four meetings. The research instrument used is a multiple choice test of 25 questions. Data obtained from this study include the value of students' high order thinking skill both in general and in every aspect. The data obtained were analyzed to obtain the average value. The result of data analysis shows that the average of students' high order thinking skill is generally good, that is 78,4. The average score of the students on the aspect of analyzing with the category was very good (82.1), evaluating with goodcategory (73,0) and creating with good category (78,6). Based on the results of the research, the LKS-assisted PBL learning model is very aptly used in training the high-class thinking ability of the class XI students at MAN Tanjung Morawa on the study of biology cell.Keyword : high order thinking skill, model PBL assisted student worksheet